The Sericothripinae genus Hydatothrips (Thysanoptera, Thripidae) in India with description of a new species - Rachana, R.r.; Amarendra, B.; Gracy, R. Gandhi (Zootaxa, 2022)
A new species of Hydatothrips is described from India, H. initium. A key to the ten species of Hydatothrips recorded from India is also provided.